Acute stress reaction, depression anxiety stress, and job withdrawal behavior in non-frontline pediatric nurses during the pandemic: a cross-sectional study - Yi, Xu; Jing, Cao; Meimei, Ma; Jianhui, Xie; Jihong, Hu; Ding, Xiang; Lihui, Zhu (Frontiers in Psychiatry, 2023)
Backgrounds: The COVID-19 pandemic has brought an unprecedented healthy crisis to the people worldwide. It is crucial to assess the psychological status of non-frontline nurses. More attention to the mental and physical health of non-frontline nurses during a public health emergency is necessary for a full understanding of the implications. Therefore, this study aims to investigate the factors that influence the acute stress reaction of non-frontline paediatric nurses during the COVID-19 pandemic. Methods: This study aimed to explore factors associated with acute stress reactions of non-frontline paediatric nurses in Hunan province during the COVID-19 pandemic. This was a cross-sectional design. 518 paediatric nurses from Hunan province, China, completed the Stanford Acute Stress Reaction Questionnaire (SASRQ), Depression Anxiety Stress Scales-21 (DASS-21), and Job Withdrawal Behavior Scales (JWB). Multiple linear regression analyses and Pearson’s correlation were used to analyse the results. Results: The mean scores of DASS-21, JWB, SASRQ were 1.443±0.500, 1.601±0.544, and 1.858±0.805, respectively. Stress, anxiety, depression (three sub-dimensions of DASS-21), JWB, monthly income and department were the major predictive factors for SASRQ (R2 = 0.592, R2 = 0.579, F = 45.473, P < 0.001). Pearson’s correlation showed that the mean score of SASRQ was positively correlated with JWB, DASS-21, and all its dimensions (P < 0.01). Conclusion: The study indicated that the SASRQ was greater with higher levels of DASS-21 and JWB. It revealed an acute stress reaction in non-frontline paediatric nurses and recommends more focus on the factors influencing the SASRQ.